An Analysis of The Word Formation Process of English Slang in The Venom Film Script: Let There Be Carnage (2021) - Shera, Lovitha Maylenia; Fitrawati, Fitrawati (Universitas Negeri Padang, 2024)
Slang Word is almost used in every conversation among young people and extends through many media and it was created and is now used largely by young people and teenagers. This is due to the fact that people react to new trends and terms more quickly and more frequently than before. Slang words can be found in movies, because slang words are informal words that, from year to year experience new slang vocabulary increases. This research is An Analysis of The Word Formation Process of English Slang in The Venom Film Script: Let There Be Carnage (2021). The purpose of this study was to find out how many Slang Words and the characteristic groupings of Slang Words found in the film script Venom: Let There Be Carnage (2021) and the Word Formation Process experienced by Slang Word. This study uses the theory of Yule (1985) and Allan and Burridge (2006). The data instrument used in this research is in the form of data collection and making a table of indicators to clarify the theory applied to this research. The method used is descriptive research by collecting and explaining the meaning of the Slang Words found. The data found are the Slang Word Characteristics there are Fresh and Creative, Flippant, Imitative, and Acronym. The Slang Word data found underwent a word formation process, there are Compounding, Borrowing, Coinage, Blending, Conversion, and Derivation. The results of this study found 44 words that belong to the characteristics of Slang Word, with the most dominant Fresh and Creative, namely 20 words (45.45%) and the least data, namely, Acronym 1 word (2.27%). From the Slang Word data it was found that only 25 words underwent a Word Formation Process with dominant compounding of 15 words (60%) and data of at least 1 word Derivation (4%).